PELATIHAN MANAJEMEN KEUANGAN RUMAH TANGGA UNTUK IBU PKK DI DESA KARYAMEKAR, PASIRWANGI, GARUT, JAWA BARAT - Eko Gumaya Sari; Taufan Gojali; Evi Erfiyana; Dedy Suryadi; Maria Evy Purwitasari (POLITEKNIK LP3I JAKARTA, 2025)
Household financial management training is one way to improve families' ability to effectively manage income, expenses, and savings. This research was conducted in Karyamekar Village, Pasirwangi, Garut, West Java, targeting women members of the Family Welfare Movement (PKK). The objective of this activity was to improve the knowledge and skills of PKK women in household budget planning, financial management, and optimal utilization of existing resources. The method used in this research was a workshop with a participatory approach, including material delivery, group discussions, and practical training on creating a household budget. Data were collected through observations, questionnaires, and interviews before and after the training. Data analysis was conducted descriptively to assess changes in participants' knowledge and skills. The results of the training indicated an increase in PKK women's understanding of the importance of household financial management. Participants were able to create simple budget plans, identify sources of expenditure, and implement efficient financial management strategies. Furthermore, this training fostered awareness of saving and optimized the use of family funds according to priority needs. Thus, the household financial management training for PKK women in Karyamekar Village positively contributed to improving family financial literacy. This activity is recommended to be continued periodically and expanded to other villages as an effort to empower families economically.